2015
DOI: 10.1103/physrevlett.115.225001
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of an Electron by a Dielectric Wall

Abstract: We introduce a method for calculating the probability with which a low-energy electron hitting the wall of a bounded plasma gets stuck in it and apply the method to a dielectric wall with positive electron affinity smaller than the bandgap using MgO as an example. In accordance with electron beam scattering data we obtain energy-dependent sticking probabilities significantly less than unity and question thereby for electrons the perfect absorber assumption used in plasma modeling.PACS numbers: 68.49. Jk, 79.20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…The influx is recorded at the minimum of φ(x) so that if an emission barrier is present, the returned electrons Γ eret do not induce emission (although repeated reflections of the low energy electrons could be possible for some materials in light of Ref. [26]). …”
Section: Figmentioning
confidence: 99%
“…The influx is recorded at the minimum of φ(x) so that if an emission barrier is present, the returned electrons Γ eret do not induce emission (although repeated reflections of the low energy electrons could be possible for some materials in light of Ref. [26]). …”
Section: Figmentioning
confidence: 99%
“…Utilizing the electron's large penetration depth at the energies of a few electron volts [47], typical for plasma applications, we showed that the chain of events described in the previous paragraph gives rise to a sticking probability S(E, ξ) which is the product of the probability T (E, ξ) for quantum-mechanical transmission through the surface potential and the probability to stay inside the surface despite of inelastic backscattering inside it [31,32]. To make the connection between absorption by and backscattering from the dielectric surface explicit, we recast the expression for S(E, ξ) in the form…”
Section: Electron Absorption and Backscatteringmentioning
confidence: 89%
“…The interaction of electrons with surfaces is central for a great variety of surface diagnostics as well as materials processing techniques. It has been studied in great detail (see references in [31,32]). This knowledge however is not of immediate use for the modeling of electron-surface interaction in plasma applications, such as, dielectric barrier discharges, Hall thrusters, or the divertor region of fusion plasmas.…”
Section: Electron Absorption and Backscatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…[210] and their stopping in the solid, as well as the electron dynamics across the interface, e.g. [20]. Here nonequlibrium quantum methods such as the quantum Boltzmann equation, density functional theory and nonequlibrium Green functions simulations, e.g.…”
Section: Discussionmentioning
confidence: 99%